2016
DOI: 10.2147/ott.s96992
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD40 is a positive prognostic factor of diffuse large B-cell lymphoma treated with R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone)

Abstract: ObjectivesThe objective of this study was to investigate the expression level of CD40 and its role in the prognosis of patients with diffuse large B-cell lymphoma (DLBCL) who were treated with rituximab-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone).Design and methodsThe immunohistochemical expressions of CD40 in 186 well-characterized DLBCL patients were evaluated by tissue microarrays, thereby revealing the relationship of the molecule CD40 with known tumor, patient-related vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Findings on CD40 are consistent with the results published by Keidai et al, in which 51.9% of NSCLC tissue specimens [24] and 78% of lung cancer cell lines (14 of 18) expressed CD40 [25]. Furthermore, the expression of CD40 has been documented in many other carcinomas, such as melanomas [26], hepatocellular carcinomas [27] thyroid [28], bladder [29], colon [30], esophageal squamous cell [31], ovarian [32], gastric [33], cervical [34], breast and pancreatic cancer [35], as well as in the vast majority of hematological malignancies [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Findings on CD40 are consistent with the results published by Keidai et al, in which 51.9% of NSCLC tissue specimens [24] and 78% of lung cancer cell lines (14 of 18) expressed CD40 [25]. Furthermore, the expression of CD40 has been documented in many other carcinomas, such as melanomas [26], hepatocellular carcinomas [27] thyroid [28], bladder [29], colon [30], esophageal squamous cell [31], ovarian [32], gastric [33], cervical [34], breast and pancreatic cancer [35], as well as in the vast majority of hematological malignancies [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be seen if this new technology will be widely accepted in lymphoma centers worldwide. In addition to COO classification, immunohistochemical (IHC) studies have identified multiple protein markers, such as CD5, Ki-67, FOXP1, HLA-I, p21, and CD40, that prospectively showed prognostic value for R-CHOP-treated DLBCL [ 13 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…54 An active CD40 signaling pathway was found to be predictive of treatment response in a phase I trial of dacetuzumab, a CD40-specific antibody with partial agonistic activity 56 and CD40 expression has generally emerged as a favorable prognostic marker in patients on CHOP or R-CHOP. [58][59][60] Our experimental data do not completely rule out tumor-cell extrinsic effects of CD40 targeting, but the comparable levels of tumor reduction in WT and RAGγc -/mice suggest that direct killing by CD40 activation is the dominant mechanism of tumor control in our model.…”
Section: Discussionmentioning
confidence: 66%